(untitled) (Czech Journal of Multidisciplinary Innovations, 2023)
This article explores the weight characteristics of Muslim Oriental spirituality in Uzbek epic poetry.In the spirituality of the Muslim East, the poems of Sariyi musaddasi matviyi makshuf, It was analyzed that the Musaddasi of Hazaji was written in the weight of mahzuf, Hazaji musaddasi axrabi maqbuzi mahzuf, Hafifi masaddasi maxbuni mahzuf, Mutaqoribi musammani mahzuf, Ramali musaddasi mahzuf, Ramali table maxbuni mahzuf weight